Konsep Urban Farming Menjadi Alternatif Kegiatan Bermain yang Menyenangkan bagi Anak Usia Dini - Koyimah, Siti (Pena Edukasia, 2023)
Urban farming activities for early childhood is a fun and very educational activity. Urban farming is the replacement of conventional farming concepts into urban farming. This agricultural concept is considered easy to do, clean from soil and mud and can be applied anywhere, including in urban areas and densely populated areas. Urban Farming education is expected to be able to reduce the level of dependence on gadgets as well as increase interest in farming from an early age. The concept of Urban Farming for early childhood can also help improve children's naturalist intelligence, train patience, foster responsibility, build emotion and empathy and become integrated learning. Through Urban Farming activities, children will be stimulated to understand the process of growing plants. Between the ages of 4 and 6, children need appropriate stimulation to enhance this developmental aspect of their abilities. Thus an opportunity arises to develop the concept of urban farming in PAUD units which is fun and can be used as a means to stimulate children's learning and development.